2007
DOI: 10.1007/s10669-007-9134-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tidal flooding on a coastal community in Semarang, Indonesia

Abstract: The article presents household vulnerability, local community adaptive capacity, and government's response to tidal flood hazard in the Semarang coastal area, Central Java Province, Indonesia. Using data gathered from a survey of households, the study revealed a number of important factors about the interaction between people and flood. The coastal community has been experiencing problems related to tidal floods. They have adapted to tidal flooding with structural measures, such as increasing the floor level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 8 publications
0
62
0
8
Order By: Relevance
“…They would ''jointly'' become the driving force towards development, develop a ''sense of shared ownership,'' and become ''managers'' of their development initiatives. Marfai et al (2008) highlight that the development of effective hazardreduction programs requires cooperation and exchange of experiences of the hazard affected community and local government. Understanding the community's unique perception and assessing their adaptive and proactive capacities is important for creating successful coastal hazard management programs.…”
Section: Discussionmentioning
confidence: 99%
“…They would ''jointly'' become the driving force towards development, develop a ''sense of shared ownership,'' and become ''managers'' of their development initiatives. Marfai et al (2008) highlight that the development of effective hazardreduction programs requires cooperation and exchange of experiences of the hazard affected community and local government. Understanding the community's unique perception and assessing their adaptive and proactive capacities is important for creating successful coastal hazard management programs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Heberger et al [11], an increase of 1.4 m in sea level will cause double mileage under inundation, which indicates that transportation is affected due to flood. In Semarang, Indonesia, Marfai et al [12] found that an increase of flood level about 0.5 m will cause disruption of accessibility and road.…”
Section: Risk Descriptionmentioning
confidence: 99%
“…Peta Titik Elevasi Kota Pekalongan dilakukan untuk melakukan estimasi sebaran daerah genangan di mana model yang dihasilkan akan mendekati kenyataan di lapangan. Asumsi yang digunakan dalam model ini adalah bahwa kenaikan muka air laut akan berpengaruh terhadap tubuh air yang berhubungan langsung dengan laut (Marfai et al, 2008).…”
Section: Metode Penelitianunclassified